Exploration of Heart Rate Recovery After Maximal Treadmill and Three-Minute All-Out Shuttle Tests in Firefighters - Benjamin J. Mendelson; Kyle T. Ebersole; Scott D. Brau; Nathan T. Ebersole (Fire)
The purpose of this study was to compare heart rate recovery (HRR) after a maximal treadmill (MAX-TM) and three-minute all-out (3MT) test between firefighters (FF) and a control (CON) group. Nine male CON and nine male FF participants completed height (m), weight (kg), body fat percent (BF%), normalized handgrip (GRIPNORM, kg/kg), and MAX-TM with direct gas analysis to capture aerobic capacity (VO2PEAK, mL/kg/min). A shuttle-sprint 3MT was used to measure critical velocity (CV, m/s) and D′ (m). Non-linear models determined HR decay (HRRτ), HR asymptote (HR∞), and HR amplitude (HRamp). Two-way GROUP (FF vs. CON) by TEST (MAX-TM vs. 3MT) repeated measures ANOVAs indicated a significant TEST (F = 7.004, p = 0.018) effect on HRamp. When divided by VO2PEAK classification (FITNESS), a significant TEST effect was observed (F = 7.661, p = 0.014) on HRamp. VO2PEAK was significantly related to CV (r = 0.583, p = 0.011), GRIPNORM (r = 0.668, p = 0.002), and BF% (r = −0.890, p < 0.001). Complete autonomic nervous system recovery may depend on the intensity of task demands and cardiorespiratory fitness.